Kandungan Hara Mikro dalam Pupuk Organik Cair Hasil Proses Pencernaan Anaerobik Limbah Industri Nata De Coco dan Kotoran Sapi serta Pengaruhnya pada Tanaman Selada - Zaitun Zaitun; M. Sri Saeni; Kooswardhono Mudikdjo; H.M.H. Bintoro Djoefri (Jurnal Agrista, 2009)
Micro Elements in Liquid Organic Fertilizer from Nata de coco Waste and Cow Manure in Aerobic Digester Processing and Its Influence to Lettuce CropABSTRACT. The objective of this experiment are to study micro elements in liquid organic fertilizer and to find optimal interval time of the liquid organic fertilizer application to increase lettuce yield. The experiment is conducted at Physical Chemistry and Environmental Laboratory of IPB and in Jabon Mekar Village, Parung, West Java. The treatment of this experiment is application of liquid fertilizer (organic fertilizer) once (S1), twice (S2), and three time a week (S3) from effluent anaerobic digester 75% nata de coco waste + 25% cow manure (T1), 50% nata de coco waste + 50% cow manure (T2), 25% nata de coco waste + 75% cow manure (T3), and 100% cow manure (T4) compared with control (inorganic fertilizer) on lettuce. The result shows that there are some micro elements in liquid organic fertilizer. The application of liquid organic fertilizer in twice a week in 100% cow manure (T4S2) gives the best lettuce yield (96,587 g).